The impact of virtual simulation on the recognition and response to the rapidly deteriorating patient among undergraduate nursing students. (March 2022) - Goldsworthy, Sandra; Muir, Nita; Baron, Sue; Button, Didy; Goodhand, Kate; Hunter, Steve; McNeill, Liz; Perez, Grace; McParland, Tammie; Fasken, Lisa; Peachey, Laurie
Abstract: A major patient safety challenge is recognition and response to deteriorating patients since early warning signs are often not detected in a timely manner. Nursing students typically learn the skills for early identification through clinical placement, but clinical placements are not guaranteed to provide exposure to deteriorating patients. Nursing students require practice with emergency scenarios to develop their competency and confidence to act in this area. This study aimed to explore the impact of a virtual simulation intervention on the recognition and response to the rapidly deteriorating patient among undergraduate nursing students. A mixed methods study involving a quasi-experimental pre/post design and focus groups. The participants were third or final year undergraduate nursing students from five university sites across four countries (Canada, England, Scotland and Australia, n  = 88). Students were randomly assigned to a treatment or control group. The treatment group received a virtual simulation intervention and participated in a focus group. The virtual simulation intervention had a significant effect on improving nursing student knowledge and clinical self-efficacy in the recognition and response to the rapidly deteriorating patient. Students reported that the virtual simulations decreased anxiety, helped them prioritize, filled gaps in their learning, and encouraged autonomous learning within a safe 'low risk' environment. Virtual simulation is an effective strategy for improving knowledge and confidence in recognizing and responding to the rapidly deteriorating patient among undergraduate nursing students. Highlights: This study demonstrates the positive impact of virtual simulation on knowledge and confidence of undergraduate nursing students from four countries. Nursing students reported that virtual simulation positively impacted learning, increased confidence and critical thinking ability. After the six-case virtual simulation intervention there were significant differences found between the control and simulation groups in both knowledge and clinical self-efficacy.